A comparison of clinical, magnetic resonance imaging and pathological findings in dogs with gliomatosis cerebri, focusing on cases with minimal magnetic resonance imaging changes‡. (19th June 2014) - Bentley, R. T.; Burcham, G. N.; Heng, H. G.; Levine, J. M.; Longshore, R.; Carrera‐Justiz, S.; Cameron, S.; Kopf, K.; Miller, M. A.
Abstract: The primary study objective was to determine whether clinical examination and magnetic resonance imaging (MRI) can underestimate canine gliomatosis cerebri (GC); we also investigated immunohistochemical features. Seven dogs with GC were studied; four recruited specifically because of minimal MRI changes. Neuroanatomic localization and the distribution of MRI, gross and sub‐gross lesions were compared with the actual histological distribution of neoplastic cells. In six cases, clinical examination predicted focal disease and MRI demonstrated a single lesion or appeared normal. Neoplastic cells infiltrated many regions deemed normal by clinical examination and MRI, and were Olig2‐positive and glial fibrillary acid protein‐negative. Four dogs had concurrent gliomas. GC is a differential diagnosis for dogs with focal neurological deficits and a normal MRI or a focal MRI lesion. Canine GC is probably mainly oligodendrocytic. Type II GC, a solid glioma accompanying diffuse central nervous system neoplastic infiltration, occurs in dogs as in people.